Dynamic postnatal development of the cellular and circuit properties of striatal D1 and D2 spiny projection neurons - Krajeski, RN; Macey‐Dare, A; Heusden, F; Ebrahimjee, F; Ellender, TJ (Wiley, 2019)
Many basal ganglia neurodevelopmental disorders are thought to result from imbalances in the activity of the D1‐expressing direct‐pathway and D2‐expressing indirect‐pathway striatal projection neurons (SPNs). Insight into these disorders is reliant on our understanding of normal D1 and D2 SPN development. Here we provide the first detailed study and quantification of the striatal cellular and circuit changes occurring for both D1 and D2 SPNs in the first postnatal weeks using in vitro whole‐cell patch‐clamp electrophysiology. Characterization of their intrinsic electrophysiological and morphological properties, the excitatory long‐range inputs coming from cortex and thalamus, as well their local gap junction and inhibitory synaptic connections reveals this period to be highly dynamic with numerous properties changing. However it is possible to make several main observations. Firstly, that many aspects of SPNs mature in parallel, including intrinsic membrane properties, increases in dendritic arbors and spine densities, general maturation of synaptic inputs and expression of specific glutamate receptors. Secondly, that there are notable exceptions, including a transient stronger thalamic innervation of D2 SPNs and stronger cortical NMDA receptor‐mediated inputs to D1 SPNs, both in the second postnatal week. Lastly, that many of the defining properties of mature D1 and D2 SPNs and striatal circuits are already established by the first and second postnatal weeks, including different electrophysiological properties as well as biased local inhibitory connections between SPNs; suggesting this is guided through intrinsic developmental programs. Together these findings provide an experimental framework for future studies of D1 and D2 SPN development in health and disease.